2017
DOI: 10.1111/imm.12733
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of murine tumour growth through CD8+ cytotoxic T lymphocytes via activated DEC‐205+ dendritic cells by sequential administration of α‐galactosylceramide in vivo

Abstract: SummaryCancer immunity is mediated through the effective priming and activation of tumour‐specific class I MHC molecule‐restricted CD8+ cytotoxic T lymphocytes (CTLs). DEC‐205+ dendritic cells (DCs) can cross‐present the epitope(s) of captured tumour antigens associated with class I MHC molecules alongside co‐stimulatory molecules to prime and activate tumour‐specific CD8+ CTLs. Immunosuppressive tolerogenic DCs with reduced co‐stimulatory molecules may be a cause of impaired CTL induction. Hepa1‐6‐1 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Additionally, as we have reported recently using murine system, the known lipid Ag a-GalCer, which specifically stimulates invariant NKT cells, can also activate DCs through CD1d molecules and induce various cytokines to regulate the internal immune systems (16). Moreover, repetitive sequential stimulation with a-GalCer in the tumor-bearing mice preferentially activates DCs rather than invariant NKT cells, and the activated DCs elicit tumor-specific CD8 + CTLs to eliminate the tumor cells in vivo (14). Thus, tumor may be attacked after sequential stimulation of CD1d molecules on the DCs through their specific lipid ligands a-GalCer in the murine system.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, as we have reported recently using murine system, the known lipid Ag a-GalCer, which specifically stimulates invariant NKT cells, can also activate DCs through CD1d molecules and induce various cytokines to regulate the internal immune systems (16). Moreover, repetitive sequential stimulation with a-GalCer in the tumor-bearing mice preferentially activates DCs rather than invariant NKT cells, and the activated DCs elicit tumor-specific CD8 + CTLs to eliminate the tumor cells in vivo (14). Thus, tumor may be attacked after sequential stimulation of CD1d molecules on the DCs through their specific lipid ligands a-GalCer in the murine system.…”
Section: Discussionmentioning
confidence: 82%
“…We have recently reported that immunosuppressive tolerogenic DCs with down-regulated co-stimulatory molecules that will inhibit tumor-specific CTL induction have been observed within tumors and seem to be induced by tumor-derived soluble factors in both mice [1] and humans [2]. However, intravenous treatment with tumor-specific MHC molecule-restricted CD8 + CTLs showing excellent in vitro cytotoxicity against tumors in mice has proven ineffective for tumor mass regression [3]. This may be because tolerogenic DCs inactivate the cytotoxicity of administered CTLs in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, internally synthesized antigenic molecules, such as viral components or tumor antigens, are presented by class I MHC molecules [4]. As shown in previous research [1, 5], it seems that most DEC-205 + DCs within the murine tumor mass became tolerogenic with down-regulated expression of co-stimulatory molecules despite the unique cross-presentation function of these DCs [3, 6, 7]. This function involves the CTL epitope within the externally captured antigens being presented with the class I MHC, and we have previously reported that such cross-presentation occurs after immunizing with proteins that have unique adjuvants, such as immune stimulating complexes (ISCOMs) [8] or cholera toxin [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antigenicity of proteins was determined by antigenic determinants and the antigenic determinants of the proteins had 2 types of sequential epitope (24,25) and conformation epitope (26). The research showed that the purified PEL-SLO fusion protein had a specialty of 1 × 10 7 HU/mg, about 10 fold of natural SLO.…”
Section: Effect Of Pectate Lyase On the Antigenicity Of Streptolysin Omentioning
confidence: 99%